Kerajinan Makrame untuk Meningkatkan Produktivitas pada Mahasiswi Jurusan PJKR - Shinta Masitho Windriyani; Asri Putri Anugraini; Paulus Rah Adi Pawitra (Lembaga Pengembangan Kinerja Dosen, 2025)
Students majoring in PJKR are closer to the world of sports, namely as extracurricular coaches according to sports, sports teachers, instructors or the like. So with this training, it is hoped that it will be able to provide other provisions for field development in business. Implementation of activities: survey of training venues and objectives; then giving a briefing to the training participants (students) of Makrame; prepare makrame training materials and tools; the implementation of makrame training; evaluation of makrame training; and reports of Makrame training service activities. The activity was carried out on the UIBU campus majoring in PJKR, held from April 10 to 21, 2025. Materials needed in makrame training include: 3mm makrame rope, hanging rings, scissors, clear plaster. The initial knowledge of PJKR students in the form of handicrafts in the form of makrame is 10%, after the training is carried out, the knowledge becomes 95%.